Flexible Metal Halide Perovskite Photodetector Arrays via Photolithography and Dry Lift‐Off Patterning. Issue 1 (16th October 2021) - Xia, Benzheng; Tu, Min; Pradhan, Bapi; Ceyssens, Frederik; Tietze, Max Lutz; Rubio-Giménez, Víctor; Wauteraerts, Nathalie; Gao, Yujie; Kraft, Michael; Steele, Julian A.; Debroye, Elke; Hofkens, Johan; et al.
Abstract : Metal halide perovskites draw increasing attention as photodetector materials due to their strong visible light absorption and resulting photocurrent. The development of efficient fabrication routes to realize high‐resolution perovskite pixel arrays is critical to enable practical devices. Herein, a dry lift‐off process to fabricate methylammonium lead iodide (MAPbI3 ) pixels on different substrates is reported, with a resolution down to 5 μm. Accordingly, 8 × 10 photodetector arrays are fabricated on both glass and flexible polyethylene terephthalate (PET). These arrays show a sensitive photoresponse over a broad wavelength range from 320 to 760 nm. Moreover, when encapsulated by a Parylene‐C overlayer, the photodetector arrays on glass substrate show remarkable air stability, without noticeable performance loss after 10 days in ambient air, and the flexible photodetector arrays on PET substrate show excellent bending tolerance, retaining nearly 95% of the response after 170 bending cycles. Abstract : Methylammonium lead iodide (MAPbI3 ) photodetector arrays are patterned on both glass and PET substrates via Parylene‐C dry lift‐off. The photodetectors show a sensitive photoresponse over a broad wavelength range, and imaging is demonstrated by tracking the movement of a light spot illuminating the array through a shadow mask.